High-strength steel, zinc-iron alloy hot-dip galvanized high-strength steel and preparation method

By optimizing the chemical composition and microstructure of high-strength steel and combining electromagnetic induction heating and tempering technology, the porosity and forming performance of high-strength steel are improved, and the shortcomings of existing high-strength steels in porosity and drawing forming are solved, and the implementation of the lack of existing high-strength steels in porosity and drawing forming is achieved. The yield strength and tensile strength are improved, while the pore reaming rate and forming ability are improved.

CN119194267APending Publication Date: 2024-12-27BEIJING SHOUGANG CO LTD +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411606220.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-strength steel has shortcomings in hole reaming performance, which is difficult to meet the needs of complex shape processing and hole reaming, especially in the forming and drawing forming of automotive parts.

Method used

By designing the chemical composition of the steel matrix, including C, Si, Mn, Al, Cr, Mo, Ti, Nb and other elements, the slat tempered martensite, isoxial ferrite and bainite microstructure are formed by forming the microstructure of the strip-like tempered martensite, isoxial ferrite and bainite , and use electromagnetic induction heating to low temperature heat treatment, and use waste heat removal to temper, promote the diffusion of C elements in hard-phase martensite, pin ferrite dislocation, improve ferrite strength and martensite softening, and improve porosity expansion rate.

Benefits of technology

The yield strength of high-strength steel is achieved at 740MPa~990MPa, tensile strength ≥1180MPa, elongation after breaking >7% and reaming rate >30%. It has good bending, flange and reaming capabilities, and is suitable for automobiles with complex shapes. Part forming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194267A_ABST
    Figure CN119194267A_ABST
Patent Text Reader

Abstract

The invention relates to high-strength steel, zinc-iron alloy hot-dip galvanized high-strength steel and a preparation method, and belongs to the field of steel preparation. A steel matrix of the high-strength steel comprises the following chemical components in percentage by mass: 0.07 to 0.15 percent of C, 0.2 to 0.5 percent of Si, 1.8 to 2.6 percent of Mn, less than or equal to 0.01 percent of P, less than or equal to 0.005 percent of S, 0.1 to 0.6 percent of Al, 0.2 to 0.6 percent of Cr and 0.1 to 0.3 percent of Mo; the alloy comprises the following components in percentage by weight: 0.01-0.04% of Ti, 0.01-0.04% of Nb and the balance of Fe and inevitable impurities. By reasonably designing the chemical components of the steel, the generated microscopic structure comprises martensite, ferrite and a very small amount of bainite structure. And then carrying out electromagnetic induction heating low-temperature heat treatment, and tempering by utilizing coiling waste heat, so that the martensite is converted into tempered martensite. And in the tempering process, the coordinated deformation capacity between a ferrite soft phase and a martensite soft and hard phase is improved, and therefore the hole expansion rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel preparation, and in particular to a high-strength steel, a zinc-iron alloy hot-dip galvanized high-strength steel and a preparation method thereof. Background Art

[0002] With the development of lightweight automobiles, energy conservation and emission reduction have become new trends in automobile development on the basis of higher requirements for automobile safety performance. For this reason, automobile steel has gradually developed towards advanced high-strength steel, and its representative steels include dual-phase steel, complex-phase steel and TRIP steel. Dual-phase steel has high strength and high toughness, that is, it has a good combination of strength and toughness. In addition, dual-phase steel has a high strength-to-yield ratio, high elongation and high work hardening rate, and no discontinuous yield phenomenon. These make it have good forming and processing performance, especially avoiding local diameter shrinkage and fracture during deep drawing and deep stamping, and is particularly suitable for cold forming such as cold rolling and cold stamping.

[0003] In recent years, with the increasing complexity of the shapes of processed parts, materials need to have not only good forming ability, but also good bending, flanging and hole expansion capabilities. Dual-phase steel provides ductility from ferrite, while martensite provides strength and hardness, and has poor hole expansion ability. Therefore, it is urgent to develop a high-strength steel with both high hole expansion performance and good forming performance to meet the common needs of hole expansion and drawing forming. Summary of the invention

[0004] The present application provides a high-strength steel, zinc-iron alloy hot-dip galvanized high-strength steel and a preparation method to solve the following technical problem: how to improve the hole expansion rate of high-strength steel.

[0005] In a first aspect, the present application provides a high-strength steel, wherein the chemical composition of the steel matrix of the high-strength steel is, by mass fraction, C: 0.07% to 0.15%, Si: 0.2% to 0.5%, Mn: 1.8% to 2.6%, P: ≤0.01%, S: ≤0.005%, Al: 0.1% to 0.6%, Cr: 0.2% to 0.6%, Mo: 0.1% to 0.3%; Ti: 0.01% to 0.04%, Nb: 0.01% to 0.04%, and the balance is Fe and unavoidable impurities;

[0006] Measured by volume fraction, the microstructure of the steel matrix includes: lath-shaped tempered martensite: 55% to 65%, equiaxed ferrite: 30% to 40%, and bainite.

[0007] Optionally, the grain size of the lath-shaped tempered martensite is 1 to 2 μm, the grain size of the equiaxed ferrite is 1 to 3 μm, and the grain size of the bainite is 0.8 to 1.2 μm.

[0008] Optionally, the chemical composition of the steel matrix, measured by mass fraction, is: C: 0.08% to 0.13%, Si: 0.3% to 0.4%, Mn: 1.9% to 2.4%, Al: 0.2% to 0.5%, Cr: 0.3% to 0.5%, Mo: 0.2% to 0.3%; Ti: 0.02% to 0.04%, Nb: 0.01% to 0.03%.

[0009] Optionally, the high-strength steel satisfies at least one of the following properties: yield strength 740MPa-990MPa, tensile strength ≥1180MPa, elongation after fracture >7%, and hole expansion rate >30%.

[0010] In a second aspect, the present application provides a zinc-iron alloy hot-dip galvanized high-strength steel, which comprises a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate; the steel substrate comprises the high-strength steel described in any one of the embodiments in the first aspect.

[0011] In a third aspect, the present application provides a method for preparing the zinc-iron alloy hot-dip galvanized high-strength steel described in the second aspect, the method comprising:

[0012] Obtaining a casting billet having the chemical composition;

[0013] The cast billet is sequentially subjected to first heating, rolling, cooling and first coiling to obtain a hot-rolled plate;

[0014] Cold rolling the hot-rolled sheet to obtain a cold-rolled sheet;

[0015] The cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel;

[0016] The primary zinc-iron alloy hot-dip galvanized high-strength steel is subjected to electromagnetic induction heating, and then immediately coiled for a second time, air-cooled or heat-insulated with a heat-insulating cover, and the residual heat of coiling is used to complete the martensitic tempering process to obtain the zinc-iron alloy hot-dip galvanized high-strength steel.

[0017] Optionally, the first heating temperature is 1250°C to 1300°C; the final rolling temperature is 850°C to 900°C; and the first coiling temperature is 520°C to 600°C.

[0018] Optionally, the cold rolling equipment contains 5 cold rolling stands, and the reduction distribution rates of the 5 cold rolling stands are: 15% to 25%, 15% to 25%, 15% to 20%, 15% to 20% and 0.3% to 1% from the beginning to the end.

[0019] Optionally, the cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel, comprising:

[0020] The cold-rolled sheet is subjected to a second heating and soaking treatment;

[0021] Slowly cooling the cold-rolled sheet after the soaking treatment;

[0022] Hot-dip galvanizing the cold-rolled sheet after slow cooling to obtain hot-dip galvanized high-strength steel;

[0023] The hot-dip galvanized high-strength steel is alloyed and heated, and then skin-finished to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel.

[0024] Optionally, the second heating temperature is 750℃~810℃, the heat treatment temperature is 750℃~810℃, the slow cooling temperature is 650℃~710℃, the hot dip galvanizing temperature is 453℃~457℃, the height of the zinc liquid level of the hot dip galvanizing is 38~42mm from the upper edge of the zinc pot, the hot dip galvanizing belt speed is 70m / min~90m / min, the alloying heating temperature is 510℃~550℃, and the elongation of the skin pass is 0.2%~0.6%.

[0025] Optionally, the initial temperature of the electromagnetic induction heated steel strip is 5°C to 40°C, the temperature of the electromagnetic induction heated steel strip is 100°C to 450°C, and the speed of the electromagnetic induction heated steel strip is 10m / min to 250m / min.

[0026] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0027] The present application provides a high-strength steel, wherein the chemical composition of the steel matrix of the high-strength steel is, by mass fraction, C: 0.07% to 0.15%, Si: 0.2% to 0.5%, Mn: 1.8% to 2.6%, P: ≤0.01%, S: ≤0.005%, Al: 0.1% to 0.6%, Cr: 0.2% to 0.6%, Mo: 0.1% to 0.3%; Ti: 0.01% to 0.04%, Nb: 0.01% to 0.04%, the remainder being Fe and unavoidable impurities; by volume fraction, the microstructure of the steel matrix comprises: lath-shaped tempered martensite: 55% to 65%, equiaxed ferrite: 30% to 40%, and bainite. By rationally designing the chemical composition of the steel, the resulting microstructure comprises martensite, ferrite, and a very small amount of bainite. After that, the martensite is transformed into tempered martensite by low-temperature heat treatment through electromagnetic induction heating and tempering using the residual heat of coiling. The tempering process causes the supersaturated C atoms in the hard phase martensite to diffuse to the interface between the soft phase ferrite and the hard phase martensite, thereby pinning the dislocations in the ferrite at the interface and improving the strength of the soft phase ferrite. At the same time, the reduction of C elements in the hard phase martensite leads to the softening of the martensite phase, thereby improving the coordinated deformation ability between the soft phase of ferrite and the soft and hard phases of martensite, and achieving an increase in the hole expansion rate. It is particularly suitable for automotive parts that require a certain forming ability and require flanging and hole expansion design. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0030] Figure 1 A schematic diagram of a process for preparing a zinc-iron alloy hot-dip galvanized high-strength steel provided in an embodiment of the present application;

[0031] Figure 2 The microstructure of the zinc-iron alloy hot-dip galvanized high-strength steel provided in the embodiment of the present application;

[0032] Figure 3 This is a diagram of the surface state of the zinc-iron alloy hot-dip galvanized high-strength steel product off the production line provided in the embodiment of the present application. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0034] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0035] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0036] In a first aspect, the present application provides a high-strength steel, wherein the chemical composition of the steel matrix of the high-strength steel is, by mass fraction, C: 0.07% to 0.15%, Si: 0.2% to 0.5%, Mn: 1.8% to 2.6%, P: ≤0.01%, S: ≤0.005%, Al: 0.1% to 0.6%, Cr: 0.2% to 0.6%, Mo: 0.1% to 0.3%; Ti: 0.01% to 0.04%, Nb: 0.01% to 0.04%, and the balance is Fe and unavoidable impurities;

[0037] Measured by volume fraction, the microstructure of the steel matrix includes: lath-shaped tempered martensite: 55% to 65%, equiaxed ferrite: 30% to 40%, and bainite.

[0038] The positive effect of controlling the C content to 0.07% to 0.15% is that C is an austenite stabilizing element, and adding too much or too little will result in too high or insufficient strength level. For example, the C content is 0.07%, 0.08%, 0.10%, 0.12%, 0.15%, etc.

[0039] The positive effect of controlling the Si content to 0.2% to 0.5% is that Si can effectively promote the diffusion of C elements in ferrite into austenite, and play a role in purifying ferrite. Si is also one of the important elements that affect the quality of the coating. Adding too much Si will cause selective oxidation of the strip, which will affect the surface quality of the strip; adding too little Si will cause insufficient elongation of the material and reduce the formability of the material. Exemplarily, the Si content is 0.2%, 0.3%, 0.4%, 0.5%, etc.

[0040] The positive effect of controlling the Mn content to 1.8% to 2.6% is that Mn is the main solid solution strengthening element and hardenability element, and is also one of the austenite stabilizing elements; too low a Mn content is not conducive to obtaining the required tensile strength, and too high a Mn content will lead to excessive alloy cost and poor strip surface quality. Exemplarily, the Mn content is 1.8%, 2.0%, 2.3%, 2.4%, 2.6%, etc.

[0041] Positive effects of controlling the P content ≤ 0.01%: P is an inevitable impurity in steel, which is easy to form micro segregation when the molten steel solidifies, and segregates to the grain boundary during the subsequent heat treatment process, which significantly increases the brittleness of the steel. The content should be controlled below 0.01%. For example, the P content can be 0.005%, 0.008%, 0.01%, etc.

[0042] The positive effect of controlling the S content ≤ 0.005%: S is an inevitable impurity in steel, which is easy to form MnS inclusions, thereby reducing the toughness and plasticity of steel. The content should be controlled below 0.005%. For example, the S content can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, etc.

[0043] Positive effects of controlling the Al content to 0.1% to 0.6%: Al can effectively promote the diffusion of C elements in ferrite into austenite, and play a role in purifying ferrite, but Al is not good for the castability of the ingot, so its content is controlled to be 0.1% to 0.6%. For example, the Al content can be 0.1%, 0.3%, 0.4%, 0.5%, 0.6%, etc.

[0044] The positive effect of controlling the Cr content to 0.2% to 0.6% is that Cr is an austenite stabilizing element, and adding too much or too little will result in too high or insufficient strength level; illustratively, the Cr content is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, etc.

[0045] Positive effects of controlling the Mo content to 0.1% to 0.3%: Mo is an austenite stabilizing element, and adding too much or too little will result in too high or insufficient strength level; illustratively, the Mo content is 0.1%, 0.2%, 0.3%, etc.

[0046] The positive effect of controlling the Ti content to 0.01% to 0.04% is that Ti is a typical microalloying element. Ti carbonitride can effectively increase the precipitation strengthening increment and improve hydrogen embrittlement sensitivity. Too much carbonitride is not conducive to improving plasticity. The Ti content of this application is controlled to 0.01% to 0.04%. For example, the Ti content can be 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0047] The positive effect of controlling the Nb content to 0.01% to 0.04% is that Nb is a typical microalloying element. The solid solution of Nb and the carbonitride formed can refine the grains. The carbonitride can also improve the hydrogen embrittlement sensitivity. However, too much carbonitride is not good for plasticity. Therefore, the Nb content of this application is controlled to be 0.01% to 0.04%. For example, the Nb content can be 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0048] Tempered martensite generally refers to the martensite structure after tempering treatment, and ferrite generally refers to the interstitial solid solution of carbon dissolved in α-Fe. Through process innovation, the microstructure morphology and phase ratio of zinc-iron alloy hot-dip galvanized high-strength steel are optimized. On the basis of obtaining lamellar martensite and equiaxed ferrite, low-temperature heat treatment is carried out by electromagnetic induction heating, and tempering is carried out by coiling residual heat, so that martensite is transformed into tempered martensite. The tempering process promotes the supersaturated C atoms in the hard phase martensite to diffuse to the interface between the soft phase ferrite and the hard phase martensite, and then pins the dislocations in the ferrite at the interface, thereby improving the strength of the soft phase ferrite. At the same time, the reduction of C elements in the hard phase martensite leads to the softening of the martensite phase, thereby improving the coordinated deformation ability between the soft phase of ferrite and the soft and hard phases of martensite, and effectively improving the hole expansion rate. For example, the volume fraction of tempered martensite may be 55%, 57%, 59%, 61%, 63%, 65%, etc., and the volume fraction of ferrite may be 30%, 32%, 34%, 36%, 38%, 40%, etc.

[0049] In some embodiments, the grain size of the lath-shaped tempered martensite is 1 to 2 μm, the grain size of the equiaxed ferrite is 1 to 3 μm, and the grain size of the bainite is 0.8 to 1.2 μm.

[0050] The positive effect of the lath-shaped tempered martensite grain size of 1 to 2 μm is that it is a collective hard phase structure. If the grain size is too large, the tensile strength of the material will be too high, and if the grain size is too small, the tensile strength will be too low.

[0051] The positive effect of the equiaxed ferrite grain size of 1 to 3 μm is that it is a soft phase structure of the matrix. If the grain size is too large, the yield strength of the material will be too low, and if the grain size is too small, the yield strength will be too high.

[0052] The positive effect of the bainite grain size of 0.8 to 1.2 μm is that it coordinates the deformation between ferrite and martensite. If the grain size is too large, the yield strength of the material will be too high, and if the grain size is too small, the yield strength will be too low to a certain extent.

[0053] In some embodiments, the chemical composition of the steel matrix is, by mass fraction: C: 0.08% to 0.13%, Si: 0.3% to 0.4%, Mn: 1.9% to 2.4%, Al: 0.2% to 0.5%, Cr: 0.3% to 0.5%, Mo: 0.1% to 0.3%; Ti: 0.02% to 0.04%, Nb: 0.01% to 0.03%.

[0054] In some embodiments, the hot-dip galvanized high-strength steel meets at least one of the following properties: yield strength 740MPa-990MPa, tensile strength ≥1180MPa, elongation after fracture>7%, and hole expansion rate>30%.

[0055] Through process innovation, the microstructure morphology and phase ratio of high-strength steel are optimized. On the basis of obtaining lath-shaped ferrite + martensite, low-temperature heat treatment is carried out through electromagnetic induction heating, and tempering is carried out using the residual heat of coiling, so as to ensure that the mechanical properties of hot-dip galvanized high-strength steel meet the yield strength of 740MPa~990MPa, tensile strength ≥1180MPa, elongation after fracture>7%, hole expansion rate>30%, and have good bending, flanging and hole expansion capabilities. Exemplarily, the yield strength can be 740MPa, 770MPa, 800MPa, 850MPa, 900MPa, 990MPa, etc., the tensile strength can be 1180MPa, 1200MPa, 1220MPa, 1240MPa, etc., the elongation after fracture can be 7.2%, 7.4%, 7.6%, 7.8%, 8.0%, 8.2%, etc., and the hole expansion rate can be 32%, 34%, 36%, 38%, 40%, 44%, etc.

[0056] In a second aspect, the present application provides a zinc-iron alloy hot-dip galvanized high-strength steel, which comprises a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate; the steel substrate comprises the high-strength steel described in any one of the embodiments in the first aspect.

[0057] Figure 1 A schematic flow chart of a method for preparing zinc-iron alloy hot-dip galvanized high-strength steel provided in an embodiment of the present application.

[0058] See also Figure 1 In a third aspect, the present application provides a method for preparing zinc-iron alloy hot-dip galvanized high-strength steel, the method comprising:

[0059] S1, obtaining a casting billet having the chemical composition;

[0060] S2, sequentially performing first heating, rolling, cooling and first coiling on the ingot to obtain a hot-rolled plate;

[0061] In some embodiments, the heating temperature is 1250°C to 1300°C; and / or the final rolling temperature is 850°C to 900°C; and / or the first coiling temperature is 520°C to 600°C.

[0062] The positive effect of controlling the heating temperature to 1250°C to 1300°C is that the homogenization of the structure and the solid solution of the micro-alloying elements can be ensured. Too high a temperature may cause abnormal grain growth, and too low a temperature may cause uneven composition and insufficient solid solution of the micro-alloying elements. Exemplarily, the heating temperature is 1250°C, 1270°C, 1290°C, 1300°C, etc.

[0063] The positive effect of controlling the final rolling temperature of rolling to 850-900°C is to ensure a good hot rolling structure and avoid excessively coarse grains and mixed crystals. Exemplarily, the final rolling temperature of the rolling is 850°C, 860°C, 870°C, 890°C, 900°C, etc.

[0064] The positive effect of controlling the temperature of the first coiling to 520-600°C is that this temperature range can achieve a hot-rolled structure of a large amount of bainite and a small amount of ferrite, and a large amount of bainite will provide more convenient conditions for the diffusion of elements in the subsequent two-phase annealing process. Exemplarily, the temperature of the first coiling can be 520°C, 540°C, 560°C, 580°C, 600°C, etc.

[0065] S3, cold rolling the hot-rolled sheet to obtain a cold-rolled sheet.

[0066] In some embodiments, the cold rolling equipment contains 5 cold rolling stands, and the reduction distribution rates of the 5 cold rolling stands are: 15% to 25%, 15% to 25%, 15% to 20%, 15% to 20% and 0.3% to 1% from the beginning to the end.

[0067] The positive effect of controlling the reduction distribution rate of the 5 cold rolling stands is as follows: the reduction distribution rate of the first 4 stands causes a large amount of material deformation to provide sufficient deformation storage energy for subsequent two-phase zone annealing; the reduction distribution rate of the 5th stand ensures that the plate shape is straight, avoiding the problem of deviation and broken strip in the subsequent furnace.

[0068] S4, annealing and hot-dip galvanizing the cold-rolled sheet to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel.

[0069] In some embodiments, the cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel, comprising:

[0070] The cold-rolled sheet is subjected to a second heating and soaking treatment;

[0071] Slowly cooling the cold-rolled sheet after the soaking treatment;

[0072] Hot-dip galvanizing the cold-rolled sheet after slow cooling to obtain hot-dip galvanized high-strength steel;

[0073] The hot-dip galvanized high-strength steel is alloyed and heated, and then skin-finished to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel.

[0074] In some embodiments, the second heating temperature is 750°C to 810°C, the soaking temperature is 750°C to 810°C, the slow cooling temperature is 650°C to 710°C, the hot-dip galvanizing temperature is 453°C to 457°C, the height of the zinc liquid level of the hot-dip galvanizing from the upper edge of the zinc pot is 38 to 42 mm, the hot-dip galvanizing belt speed is 70 m / min to 90 m / min, the alloying heating temperature is 510°C to 550°C, and the skin-pass elongation is 0.2% to 0.6%.

[0075] The positive effect of controlling the second heating temperature between 750°C and 810°C is as follows: ensuring that the material is annealed in the critical zone and the microstructure can fully recover to recrystallization. For example, the temperature of the heat treatment can be 750°C, 760°C, 770°C, 800°C, 810°C, etc.

[0076] The positive effect of controlling the soaking temperature between 750°C and 810°C is to ensure that the material is annealed in the critical region and the microstructure can be fully recovered to recrystallization. For example, the soaking temperature can be 750°C, 760°C, 770°C, 800°C, 810°C, etc.

[0077] The positive effect of controlling the slow cooling temperature to 650°C to 710°C is that the content of ferrite can be adjusted. Exemplarily, the slow cooling temperature is 650°C, 690°C, 700°C, 710°C, etc.

[0078] The temperature of hot-dip galvanizing is the temperature of the strip entering the zinc pot, which is controlled to be 453°C to 457°C, and the belt speed is 70m / min to 90m / min. The positive effect is: improving the quality of the galvanized layer. Exemplarily, the hot-dip galvanizing temperature is 453°C, 455°C, 456°C, 457°C, 460°C, etc., and the hot-dip galvanizing belt speed is 70m / min, 75m / min, 80m / min, 85m / min, 90m / min, etc.

[0079] The positive effect of controlling the alloying heating temperature to 510°C to 550°C is to ensure that the Zn-Fe reaction is sufficient. For example, the alloying temperature can be 520°C, 540°C, 560°C, 580°C, 600°C, etc.

[0080] The positive effect of controlling the elongation of the finishing to 0.2% to 0.6% is to ensure that the surface of the material has a certain roughness and yield strength. For example, the finishing elongation can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, etc.

[0081] S5. The primary zinc-iron alloy hot-dip galvanized high-strength steel is subjected to electromagnetic induction heating, and then immediately coiled for a second time, air-cooled or heat-insulated with a heat-insulating cover, and the residual heat of coiling is used to complete the martensitic tempering process to obtain the zinc-iron alloy hot-dip galvanized high-strength steel.

[0082] In some embodiments, the initial temperature of the electromagnetic induction steel strip is 5° C. to 40° C., the temperature of the electromagnetic induction heating is 100° C. to 450° C., and the belt speed of the electromagnetic induction heating is 10 to 250 m / min.

[0083] The positive effect of controlling the induction heating temperature to 100°C to 450°C is to ensure that C atoms are fully diffused between ferrite and martensite, pinning dislocations and improving yield strength. For example, the initial temperature of the strip can be 100°C, 150°C, 200°C, 300°C, 450°C, etc.

[0084] The specific chemical composition and process conditions in the embodiments of the present invention are mainly determined for the development of hot-dip galvanized steel sheets for automobiles, but the concept of the present invention is also applicable to medium and thick plates, profiles, and rods and wires.

[0085] The product prepared by the method for preparing zinc-iron alloy hot-dip galvanized high-strength steel is the above-mentioned zinc-iron alloy hot-dip galvanized high-strength steel. The chemical composition and microstructure of the zinc-iron alloy hot-dip galvanized high-strength steel prepared by the method for preparing zinc-iron alloy hot-dip galvanized high-strength steel can refer to the above-mentioned embodiment. Since the method for preparing zinc-iron alloy hot-dip galvanized high-strength steel adopts part or all of the technical solutions of the zinc-iron alloy hot-dip galvanized high-strength steel embodiment, it at least has all the beneficial effects brought by the technical solutions of the zinc-iron alloy hot-dip galvanized high-strength steel embodiment, which will not be repeated here one by one.

[0086] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0087] The molten steel is smelted in a converter to obtain the chemical composition of zinc-iron alloy hot-dip galvanized high-strength steel, as shown in Table 1.

[0088] Table 1 Chemical composition (wt%) of the steel matrix of zinc-iron alloy hot-dip galvanized high-strength steel, the remainder being Fe and unavoidable impurities

[0089] Group C Si Mn P S Al Cr Mo Ti Nb Example 1 0.09 0.25 2.2 0.008 0.005 0.18 0.38 0.22 0.015 0.038 Example 2 0.11 0.35 2.4 0.007 0.004 0.22 0.45 0.29 0.021 0.035 Example 3 0.12 0.4 2.47 0.006 0.004 0.35 0.42 0.28 0.018 0.037 Example 4 0.095 0.36 2.35 0.006 0.005 0.33 0.37 0.25 0.0021 0.036 Example 5 0.106 0.38 2.33 0.007 0.004 0.4 0.46 0.24 0.0022 0.035 Comparative Example 0.12 0.38 2.43 0.007 0.005 0.27 0.43 0.27 0.020 0.036

[0090] Based on the chemical composition of the steel matrix of the embodiment and the comparative example, this embodiment also provides a method for preparing zinc-iron alloy hot-dip galvanized high-strength steel, comprising the following steps:

[0091] Obtaining a casting billet having the chemical composition;

[0092] The cast billet is sequentially subjected to first heating, rolling, cooling and first coiling to obtain a hot-rolled plate;

[0093] Cold rolling the hot-rolled sheet to obtain a cold-rolled sheet;

[0094] The cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel;

[0095] The primary zinc-iron alloy hot-dip galvanized high-strength steel is subjected to electromagnetic induction heating and a second coiling to obtain zinc-iron alloy hot-dip galvanized high-strength steel. The process parameters of electromagnetic induction heating are shown in Table 2.

[0096] Table 2 Induction heating process and mechanical properties of the examples

[0097] Group Induction heating temperature / ℃ Yield strength / MPa Tensile strength / MPa Elongation / MPa Hole expansion rate / % Example 1 130 933 1243 8.1 32 Example 2 250 963 1235 7.8 36 Example 3 300 989 1226 7.9 43 Example 4 170 945 1244 7.9 32 Example 5 210 957 1233 8.0 34 Comparative Example - 710 1223 6.5 22

[0098] It can be seen from Tables 1 to 2 that the chemical composition and induction heating process of the embodiments are within the required range of the present invention, with a yield strength of 740 MPa to 990 MPa, a tensile strength of ≥1180 MPa, an elongation after fracture of >7%, a hole expansion rate of >30%, and a good surface quality.

[0099] Attached Figure 2-3 Detailed description:

[0100] Figure 2 The microstructure of the zinc-iron alloy hot-dip galvanized high-strength steel provided in the embodiment of the present application; Figure 2 As shown, the raised part of the matrix is ​​tempered martensite structure, and the concave part is ferrite structure.

[0101] Figure 3 The surface state diagram of the zinc-iron alloy hot-dip galvanized high-strength steel product off-line provided in the embodiment of the present application; Figure 3 As shown, there is no surface defect and it can meet the standard requirements.

[0102] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0103] The zinc-iron alloy hot-dip galvanized high-strength steel provided in the embodiment of the present invention has high hole expansion performance and good formability, a yield strength of 740MPa-990MPa, a tensile strength ≥1180MPa, an elongation after fracture >7%, a hole expansion rate >30%, and good surface quality.

[0104] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A high-strength steel, characterized in that: The chemical composition of the steel matrix of the high-strength steel is, by mass fraction, C: 0.07% to 0.15%, Si: 0.2% to 0.5%, Mn: 1.8% to 2.6%, P: ≤0.01%, S: ≤0.005%, Al: 0.1% to 0.6%, Cr: 0.2% to 0.6%, Mo: 0.1% to 0.3%; Ti: 0.01% to 0.04%, Nb: 0.01% to 0.04%, the balance is Fe and unavoidable impurities; Measured by volume fraction, the microstructure of the steel matrix includes: lath-shaped tempered martensite: 55% to 65%, equiaxed ferrite: 30% to 40%, and bainite.

2. The high-strength steel according to claim 1, characterized in that: The grain size of the lath-shaped tempered martensite is 1 to 2 μm, the grain size of the equiaxed ferrite is 1 to 3 μm, and the grain size of the bainite is 0.8 to 1.2 μm.

3. The high-strength steel according to claim 1, characterized in that: The chemical composition of the steel matrix is, by mass fraction, C: 0.08% to 0.13%, Si: 0.3% to 0.4%, Mn: 1.9% to 2.4%, Al: 0.2% to 0.5%, Cr: 0.3% to 0.5%, Mo: 0.2% to 0.3%; Ti: 0.02% to 0.04%, Nb: 0.01% to 0.03%.

4. The high-strength steel according to claim 1, characterized in that: The high-strength steel meets at least one of the following properties: yield strength of 740MPa to 990MPa, tensile strength ≥1180MPa, elongation after fracture>7%, and hole expansion rate>30%.

5. A zinc-iron alloy hot-dip galvanized high-strength steel, characterized in that: The zinc-iron alloy hot-dip galvanized high-strength steel comprises a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate; the steel substrate comprises the high-strength steel according to any one of claims 1 to 4.

6. A method for preparing the zinc-iron alloy hot-dip galvanized high-strength steel according to claim 5, characterized in that: The method comprises: Obtaining a casting billet having the chemical composition; The cast billet is sequentially subjected to first heating, rolling, cooling and first coiling to obtain a hot-rolled plate; Cold rolling the hot-rolled sheet to obtain a cold-rolled sheet; The cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel; The primary zinc-iron alloy hot-dip galvanized high-strength steel is subjected to electromagnetic induction heating, and then immediately coiled for a second time, air-cooled or heat-insulated with a heat-insulating cover, and the residual heat of coiling is used to complete the martensitic tempering process to obtain the zinc-iron alloy hot-dip galvanized high-strength steel.

7. The method according to claim 6, characterized in that The first heating temperature is 1250° C. to 1300° C.; and / or, The final rolling temperature of the rolling is 850°C to 900°C; and / or, The first coiling temperature is 520°C to 600°C; and / or, The cold rolling equipment comprises 5 cold rolling stands, and the reduction distribution rates of the 5 cold rolling stands are 15% to 25%, 15% to 25%, 15% to 20%, 15% to 20% and 0.3% to 1% from the beginning to the end.

8. The method according to claim 6, characterized in that The cold-rolled sheet is subjected to annealing and hot-dip galvanizing treatment to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel, comprising: The cold-rolled sheet is subjected to a second heating and soaking treatment; Slowly cooling the cold-rolled sheet after the soaking treatment; Hot-dip galvanizing the cold-rolled sheet after slow cooling to obtain hot-dip galvanized high-strength steel; The hot-dip galvanized high-strength steel is alloyed and heated, and then skin-finished to obtain primary zinc-iron alloy hot-dip galvanized high-strength steel.

9. The method according to claim 8, characterized in that The second heating temperature is 750℃~810℃, the soaking treatment temperature is 750℃~810℃, the slow cooling temperature is 650℃~710℃, the hot-dip galvanizing temperature is 453℃~457℃, the height of the zinc liquid level of the hot-dip galvanizing is 38~42mm from the upper edge of the zinc pot, the hot-dip galvanizing belt speed is 70m / min~90m / min, the alloying heating temperature is 510℃~550℃, and the skin-pass elongation is 0.2%~0.6%.

10. The method according to claim 6, characterized in that The initial temperature of the electromagnetic induction heated steel strip is 5°C to 40°C, the electromagnetic induction heated temperature is 100°C to 450°C, and the electromagnetic induction heated steel strip speed is 10m / min to 250m / min.

Citation Information

Cited By

  • High-reaming 980MPa-grade hot-dip galvanized high-strength steel and preparation method thereof

    CN119913424A